A Re-examination of the Impact of Credit on Economic Growth in Malaysia: Further Evidence from the Asymmetric ARDL Cointegration Technique - Hussin Abdullah; Shehu El-Rasheed (Cahaya Abadi Publisher, 2023)
Earlier studies on the relationship between credit and economic growth hardly unveil the asymmetric effects of domestic credit on economic growth. This paper attempt to cover the limitation of the earlier studies by re-investigating the asymmetric effect of domestic credit on economic growth in Malaysia over the period 1980-2019. Using a recently developed asymmetric ARDL methodology, the study found an evidence of a significant asymmetric effect of domestic credit on economic growth. A long run asymmetric cointegration between domestic credit and economic growth was established. The data also reveals that domestic credit tends to have a greater impact on economic growth. The policy implication of this study is that Malaysian policy makers need to enhance and further develop its credit policies to make them more efficient and flexible so as to realize a sustainable economic growth.